Improvement of Biocatalytic Properties and Cytotoxic Activity of L-Asparaginase from Rhodospirillum rubrum by Conjugation with Chitosan-Based Cationic Polyelectrolytes - Natalia V. Dobryakova; Dmitry D. Zhdanov; Nikolay N. Sokolov; Svetlana S. Aleksandrova; Marina V. Pokrovskaya; Elena V. Kudryashova (MDPI AG, 2022)
L-asparaginases (L-ASNases, EC 3.5.1.1) are a family of enzymes that are widely used for the treatment of lymphoblastic leukemias. L-ASNase from Rhodospirillum rubrum (RrA) has a low molecular weight, low glutaminase activity, and low immunogenicity, making it a promising enzyme for antitumor drug development. In our work, the complex formation and covalent conjugation of the enzyme with synthetic or natural polycationic polymers was studied. Among non-covalent polyelectrolyte complexes (PEC), polyethyleneimine (PEI) yielded the highest effect on RrA, increasing its activity by 30%. The RrA-PEI complex had increased stability to trypsinolysis, with an inactivation constant decrease up to 10-fold compared to that of the native enzyme. The covalent conjugation of RrA with chitosan-PEI, chitosan-polyethylene glycol (chitosan-PEG), and chitosan-glycol resulted in an increase in the specific activity of L-asparagine (up to 30%). RrA-chitosan-PEG demonstrated dramatically (by 60%) increased cytotoxic activity for human chronic myeloma leukemia K562 cells in comparison to the native enzyme. The antiproliferative activity of RrA and its conjugates was significantly higher (up to 50%) than for that of the commercially available EcA at the same concentration. The results of this study demonstrated that RrA conjugates with polycations can become a promising strategy for antitumor drug development.